AN ANALYSIS OF BRITISH AND AMERICAN ENGLISH PRONUNCIATION PREFERENCES AMONG INDONESIAN STUDENTS - Syazwina, Zahfira; Munawwaroh, Wardah; Indira, Indira; Audina, Nia; Sinurat, Bloner (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study investigates how phonological awareness and high-frequency vocabulary practice can support English language learning among university students. Recognizing that pronunciation and spelling variations between American English (AmE) and British English (BrE) often pose challenges for learners, this research integrates phonological training with exposure to 100 high-frequency words. Over five days, 30 English department students participated in structured learning sessions involving pronunciation drills using International Phonetic Alphabet (IPA) transcriptions, comparative analysis of spelling differences, and interactive discussions on phonological patterns. Pre- and post-tests were administered to measure improvements in pronunciation accuracy and spelling recognition. The findings reveal substantial gains in students’ pronunciation accuracy, increased awareness of English spelling variations, and enhanced confidence in oral and written communication. These results underscore the value of incorporating phonology-focused approaches in vocabulary learning, bridging the gap between theoretical knowledge of language systems and practical communicative competence.